Dementia Knowledge Assessment Tool: Development and preliminary testing with aged care staff and family carers (vol 13, pg 248, 2014) - Toye, Christine; Lester, L.; Popescu, A.; McInerney, F.; Andrews, S.; Robinson, A. (Sage Publications Ltd., 2016)
“In Table 2, the item ‘Knowing likely cause helps to predict’ is presented under the heading ‘Incorrect statements’ when it should be shown under the heading ‘Correct statements'”.